2007
DOI: 10.1562/0031-8655(2002)0750633nipboa2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared Photosensitizer Based on a Cycloimide Derivative of Chlorin p6: 13,15-N-(3′-Hydroxypropyl)Cycloimide Chlorin p6¶

Abstract: The 13,15‐N‐(3′‐hydroxypropylcycloimide) chlorin p6 (CIC), which absorbs at 711 nm, possesses considerable photoinduced cell‐killing activity. It is 43‐, 61‐ and 110‐fold more active than chlorin p6, 3‐formyl‐3‐devinyl chlorin p6 and Photogem, respectively, and has no cytotoxicity without irradiation as estimated on A549 human adenocarcinoma cells. To attain the highest intracellular penetration and activity the monomeric form of CIC should be stabilized. This stabilization in an aqueous environment can be ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…If mitochondria have been traditionally considered as the most possible PDT target, our data have shown that the Golgi apparatus might also be a target for photodynamic treatment. This is in agreement with the accumulating data indicating that different hydrophobic photosensitizers such as ZnPC (Fabris et al, 2001), pheophorbide‐a methylester (Matroule et al, 2001), chlorine p6 derivative (Feofanov et al, 2002), Photofrin (Hsieh et al, 2003), Foscan (Teiten et al, 2003), or 2,4,5,7‐tetrabromrodamine 123 bromide (Ogata et al, 2003) can target Golgi apparatus. PDT‐induced Golgi dysfunction may lead to apoptosis (Matroule et al, 2001; Ogata et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…If mitochondria have been traditionally considered as the most possible PDT target, our data have shown that the Golgi apparatus might also be a target for photodynamic treatment. This is in agreement with the accumulating data indicating that different hydrophobic photosensitizers such as ZnPC (Fabris et al, 2001), pheophorbide‐a methylester (Matroule et al, 2001), chlorine p6 derivative (Feofanov et al, 2002), Photofrin (Hsieh et al, 2003), Foscan (Teiten et al, 2003), or 2,4,5,7‐tetrabromrodamine 123 bromide (Ogata et al, 2003) can target Golgi apparatus. PDT‐induced Golgi dysfunction may lead to apoptosis (Matroule et al, 2001; Ogata et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Air‐equilibrated samples of methylene blue (11.7 μ M in buffer), 2 (8.3 μ M in 0.1 or 1% CrEL), 3 (8.9 μ M in 0.1 or 1% CrEL), 4 , (5.6 μ M in 0.1 or 1% CrEL) and 5 (6.9 μ M in 0.3 or 1% CrEL) were supplemented with RNO (30 μ M ) and histidine (10 m M ) in 50 m M Tris‐HCI (pH 7.4) and irradiated with the He‐Ne laser (543.5 nm, 0.6 mW/cm 2 , 2 h). Other details of the measurements and calculations have been described elsewhere (1). The RNO‐based assay in the absence of histidine was used under the same experimental conditions for the detection of *OH radicals.…”
Section: Methodsmentioning
confidence: 99%
“…To probe the state of lysosomes and mitochondria after irradiation, the cells were loaded with 4 or 5 , irradiated and stained with a mixture of ethidium bromide (EtBr; 5 ng/mL) and Rh123 (50 ng/mL) or AO (0.5 μg/mL). To clarify the type of cell death, the procedure of the PE‐annexin‐EtBr staining of the cells was performed as described previously (1). The functioning of lipid transport was checked with the following procedure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations